Industrial Expansion: Sebagai Komitmen G20 Dalam Mengentaskan Kemiskinan di Negara Berkembang - Ilham Aji Pangestu; Inas Sofia Latif; Rizgita Nurul Fauzyah; Dian Yulviani (Politeknik Kesejahteraan Sosial Bandung, 2023)
Poverty is one of the most common problems in every country. The achievement of the Millennium Development Goals (MDGs) regarding the eradication of poverty is indeed indicated to have made good progress. Nevertheless, poverty alleviation remains one of the core agendas for the implementation of the Sustainable Development Goals (SDGs). As a form of contribution to the SDGs, the G20 is expected to have strategies related to poverty alleviation. This study aims to examine and discuss the concept of joint industrial expansion as a solution to the G20 in poverty alleviation in developing countries. The method used in this study is a literature review with conceptual review techniques and a qualitative approach. The results showed that the concept of joint industrial expansion is a concept where developed countries and developing countries that are members of the G20 work together to expand industries that previously existed or have been running in developed countries to be applied in developing countries while still making adjustments to the potential of member countries. It can also be done by building a new industry by looking at the potential of the place where the industry will be built. Therefore, all G20 member countries and all relevant parties must work together in the implementation of joint industrial expansion, so that the results obtained are appropriate and can reduce poverty in developing countries.